Morphological, physiological, and molecular scion traits are determinant for salt-stress tolerance of grafted citrus plants - Vives-Peris, Vicente; López-Climent, María F.; Moliner-Sabater, María; Gómez-Cadenas, Aurelio; Pérez-Clemente, Rosa M. (Frontiers in Plant Science, 2023)
Citrus productivity has been decreasing in the last decade in the Mediterranean basin as a consequence of climate change and the high levels of salinity found in the aquifers. Citrus varieties are cultivated grafted onto a rootstock, which has been reported as the responsible for plant tolerance to adverse situations. However, other important factors for stress tolerance relying in the scion have been less studied. The aim of this study was to evaluate the effect of the grafted scion on citrus tolerance to salt stress. Four different citrus rootstock/scion combinations were subjected to salt stress for 30 days, using Carrizo citrange (CC) or Citrus macrophylla (CM) as rootstocks, and Navelina orange (NA) or Oronules mandarin (OR) as scions. CM-OR was the most tolerant combination, whereas CC-NA was the most sensitive one. Our results support that the rootstock plays an important role in salt stress tolerance, but scion is also crucial. Thus, photosynthesis and transpiration, processes regulated by abscisic acid and jasmonic acid, are determinant of plant performance. These photosynthetic parameters were not affected in plants of the salt tolerant combination CM-OR, maybe due to the lower intoxication with Cl- ions, allowing a better performance of the photosynthetic machinery under stress conditions. The different stomatal density of the two citrus scions used in this work (higher in the sensitive NA in comparison to the tolerant OR) also contributes to the different tolerance of the grafted plants to this adverse condition. Additionally, CsDTX35.1 and CsDTX35.2, genes codifying for Cl- tonoplast transporters, were exclusively overexpressed in plants of the salt tolerant combination CM-OR, suggesting that these transporters involved in Cl- compartmentalization could be crucial for salt stress tolerance. It is concluded that for improving citrus tolerance to high salinity, it is important that scions have a versatile photosynthetic system, an adequate stomatal density and a proper modulation of genes coding for Cl- transporters in the tonoplast.